Multi-source research designs on ethical leadership: A literature review - Magalhães, Anabela (2019)
The aim of this article is to undertake a systematic literature review (SLR) of empirical research that uses multi‐source methods for collecting data about Ethical Leadership (EL). Research on this sensitive subject benefits from the inclusion of data from more than one source, in order to be better supported, and thus contribute to a deeper understanding of leadership and business ethics issues. The search strategy retrieved a total of 50 multi‐source empirical studies on the topic of EL, published until December 2017. This SLR shows that (a) research on EL has focused mostly on the perceptions of followers, possibly because they are the most accessible target of its outcomes, thus restricting the scope of this body of research; (b) EL is studied mainly through consideration of its consequences, a restriction that hinders explanation of the causal processes involved in ethical leadership, which remains a research arena in need of development. The systematic inclusion of other stakeholders in multi‐source methods is advanced as a way to further develop the field.